Age constraints on Tarkwaian palaeoplacer and lode-gold formation in the Tarkwa-Damang district, SW Ghana - Pigois, J.; Groves, D.; McNaughton, Neal; Snee, L. (Springer, 2003)
Two major epigenetic gold-forming events are recorded in the world-class gold province of southwest Ghana. A pre-Tarkwaian event was the source of the world-class Tarkwa palaeoplacers whereas post-Birimian and Tarkwaian deformation, which was related to the Eburnean orogeny, gave rise to the world-class (e.g. Prestea) to giant (e.g. Obuasi) orogenic gold deposits which have made the region famous for more than 2,500 years. A maximum age of 21334 Ma for Tarkwaian sedimentation is provided by 71 of 111 concordant SHRIMP II U-Pb dates from detrital zircons in Tarkwaian clastic rocks from Damang and Bippo Bin, northeast of Tarkwa. The overall data distribution broadly overlaps the relatively poorly constrained ages of Birimian volcanism and associated Dixcove-type granitoid emplacement, indicating syntectonic development of the Tarkwaian sedimentary basin. These zircon ages argue against derivation of the palaeoplacer gold from an orogenic gold source related to the compressional phase of an orogeny significantly older than the Eburnean orogeny. Instead, they suggest that the gold source was either orogenic gold lodes related to an earlier compressional phase of a diachronous Eburneanorogeny or ca. 2200-2100 Ma intrusion-related goldlode. The CO2-rich fluid inclusions in associated vein quartz pebbles are permissive of either source. At the Damang deposit, an epigenetic, orogenic lode-gold system clearly overprinted, and sulphidised low-grade palaeoplacerhematite-magnetite gold occurrences in the Banket Series conglomerate within the Tarkwaian sedimentary sequence. Gold mineralisation is demonstrably post-peak metamorphism, as gold-related alteration assemblages overprint metamorphic assemblages in host rocks. In alteration zones surrounding the dominant, subhorizontal auriferous quartz veins, there are rare occurrences of hydrothermal xenotime which give a SHRIMP U-Pb age of 20639 Ma for gold mineralisation. The similar structural timing of epigenetic gold mineralisation in Tarkwaian host rocks at Damang to that in mainly Birimian host rocks elsewhere in southwest Ghana, particularly at Obuasi, suggests that 20639 Ma is the best available age estimate for widespread orogenic gold mineralisation in the region. Argon-argon ages of 20294 and 20344 Ma for hydrothermal biotite from auriferous quartz veins appear to represent uplift and cooling of the region below about 300 C, as estimates of the temperature of gold mineralisation are higher, at around 400 C. If peak metamorphism, with temperatures of about 550 C, is assumed to have occurred at about 2100 Ma, the biotite ages, in combination with the xenotime age, suggest a broadly constant uplift rate for the region of about 1 km per 10 million years from about 2100 to 2025 Ma.